Sin City gangsters: the rise and decline of the mob in Las Vegas - Sussman, Jeffrey (Rowman & Littlefield, 2022)
"Sin City Gangsters is an exciting page-turner about how the mob created and controlled modern Las Vegas and then lost it to Corporate America"--